Association behaviors of amphiphilic polyelectrolytes and interactions between oppositely charged polymers and surfactants - Wang, Chang (2008)
Potentiometric titration and laser light scattering were used to study the association and neutralization behaviors of hydrophobically modified, random, cross-linked and block methacrylic acid-ethyl acrylate copolymers in aqueous medium.